'Families and Relationships' e-Special Issue Introduction. (August 2018) - May, Vanessa; Dawson, Matt
This 'Families and Relationships' e-Special Issue contains a selection of 10 articles previously published in Sociology . In this Introduction, we first outline the broader sub-disciplinary context and explain our selection criteria. The increased popularity of families and relationships as a focus of sociological study is reflected in the dominance of articles published in the 1990s and later. Our selection highlights the following developments within the field: the shift from the sociology of the family to a sociology of families; the debates surrounding late modernity and the individualisation thesis; increased diversity regarding types of family and kinds of issue that have been researched; and continued theoretical development that has widened the scope of study. We include reflections on how the selected articles speak to developments in the discipline at large and in the field of families and relationships, as well as what the future might hold for the field.